Effect of Storage Conditions and Activation on Growth Factor Concentration in Platelet‐Rich Plasma. Issue 4 (19th November 2019) - Kim, Joong Il; Bae, Hyun Cheol; Park, Hee Jung; Lee, Myung Chul; Han, Hyuk Soo
ABSTRACT: This study aimed to evaluate growth factor concentration in platelet‐rich plasma (PRP) (leukocyte‐rich PRP) based on storage temperature, duration of storage, and method of activation. PRP samples were stored at 24℃ (room temperature group), 4℃ (refrigerator group), and −70℃ (deep‐freezer group). In each temperature, four aliquots were prepared based on the time of analysis (immediately, 1, 3, and 7 days after preparation). After storage, concentrations of platelet‐derived growth factor‐AA (PDGF‐AA), transforming growth factor‐β (TGF‐β), vascular endothelial growth factor (VEGF), insulin‐like growth factor‐1 (IGF‐1), and fibroblast growth factor‐basic (FGF‐B) were assessed with/without activation using Quantikine colorimetric sandwich immunoassay kits. PRP was activated with 10% Triton‐X for PDGF‐AA, VEGF, FGF‐B, IGF‐1 measurement and sonication for TGF‐β1 measurement. Without activation, PDGF‐AA concentration was highest on day 7 in the room temperature group. With activation, the concentration of PDGF‐AA was constant over the observation period at all temperatures. Without activation, the TGF‐β1 concentration remained negligible over the observation period at all temperatures. However, with activation, TGF‐β1 gradually increased to its highest concentration on day 7 at all temperatures. Over the observation period, VEGF and IGF‐1 concentrations were constant with and without activation at all temperatures. Without activation, FGF‐B concentration increased, with the highest concentration observed on day 7 in the deep‐freezer group. With activation, FGF‐B concentration decreased after day 1 in the room temperature group. Growth factor concentration in PRP differed significantly based on storage temperature, duration of storage, and method of activation. Appropriate storage conditions and activation are important to optimize its effects on desired clinical outcomes. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:777‐784, 2020